Stroke in the young - Kumar, Gyan (Henry Stewart Talks, 2021)
Scope and epidemiology of stroke in the young, Risk factors and etiology, TOAST classification, Cervical artery dissection, Primary hypercoagulable states and other determined etiologies, Patent foramen ovale, RoPE score, Overlap between young stroke and cryptogenic stroke, Reperfusion therapy and secondary prevention